PERAN PROGRAM ASISTENSI MENGAJAR DALAM MENINGKATKAN KOMPETENSI KEGURUAN PADA MAHASISWA PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR - Joen Parningotan Purba; Reflina Sinaga; Liskawaty Manullang; Theresia; Nora Wita Purba; Wido Munthe; Dahlia F. Simanullang (Journal of Golden Generation Education, 2025)
The Independent Learning Campus Independent Program (MBKM) is a government initiative to improve the quality of higher education through off-campus learning activities, one of which is the Teaching Assistance program. This study aims to describe the role of the Teaching Assistance program in improving the teaching competence of students of the Elementary School Teacher Education Study Program (PGSD). The study used a descriptive qualitative approach with data collection methods through interviews, observations, and documentation. The results of the study showed that the Teaching Assistance program significantly supported the improvement of four dimensions of student teaching competence, namely pedagogical, professional, personality, and social competence. Students gain direct experience in the world of education, practice teaching skills, prepare learning tools, and build positive communication and interaction with school residents. In addition, students also develop character and personality as prospective professional educators. Thus, the Teaching Assistance program has proven to be an effective strategy in preparing competent PGSD graduates who are ready to face the real world of education work.